2005
DOI: 10.1017/s1041610205001651
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cognitive performance: a longitudinal study of older Japanese Americans. The Kame Project

Abstract: This study provides further support regarding the beneficial effects of moderate alcohol consumption on cognitive performance over time. Observed benefits were not modified by gender. Future studies need to determine whether alcohol preserves cognition directly or whether other factors such as physiology or cultural drinking practices are driving the observed association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 13 publications
4
38
0
1
Order By: Relevance
“…Our findings are in agreement with other recent prospective studies showing that alcohol intake may decrease the risk of cognitive decline [1,13,29] . One prospective study found no effect, but they used the Mini Mental State Exam, which lacks sensitivity [14] .…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in agreement with other recent prospective studies showing that alcohol intake may decrease the risk of cognitive decline [1,13,29] . One prospective study found no effect, but they used the Mini Mental State Exam, which lacks sensitivity [14] .…”
Section: Discussionsupporting
confidence: 93%
“…This improvement specifically encompasses baseline attention, processing speed, which is the ability to perform tasks requiring rapid visual scanning and mental processing of information, memory such as verbal knowledge or memory including immediate and delayed recall, recognition memory, figural memory and working memory, as well as motor speed. This has been observed for both men and women [62,[66][67][68][69]. Gross et al (2011) concluded that that the consumption of alcoholic beverages three to four times per week or low levels of drinks per week through midlife and into later life, confers the best cognitive outcomes in old age, as defined by wordfinding ability in late life, a measure of executive function [70].…”
Section: Relationship Of Alcoholic Beverages To Cognitive Function Anmentioning
confidence: 97%
“…In various cross-sectional and longitudinal studies, better cognitive performance in older adults has been found to be associated with: (i) socioeconomic status (younger age, female or male gender, higher education, greater wealth, population group); [3][4][5] (ii) illness conditions and health status (fewer depressive symptoms, no hypertension, no cardiovascular disease, particularly heart failure, no type 2 diabetes, no insomnia, no malnourishment, better quality of life (QoL) and life satisfaction); 6-13 (iii) social coherence and contact (attendance at religious gatherings); 4,14 and (iv) healthy behaviour (physical activity, no smoking and moderate alcohol use). [15][16][17][18][19][20] We aimed to investigate cognitive functioning and associated factors in a national probability sample of older South Africans who participated in the Study of Global AGEing and Adult Health (SAGE) in 2008. …”
mentioning
confidence: 99%